The use of social media bot accounts on influencing public opinion: a legal review in Indonesia - Devi Rahma Fatmala; Amanda Amelia; Fitri Agustina Trianingsih (Faculty of Law, University of Muhammadiyah Malang, 2020)
Today’s political discourse cannot be separated from the usage of social media. There are plenty of political actors using it to campaign their issues and attack their political rivals to influence public opinion. One of the instruments used by the political actor in using social media is bot accounts. Bot accounts are an automated online account where all or substantially all of the actions or posts of that account are not the result of a person. The usage of bot accounts is viewed as harmful for democracy by many experts on law and democracy. However, lots of states have no regulation regarding the usage of bot accounts, including Indonesia. This article intends to bring legal review on the usage of bot accounts to influence public opinion in Indonesia. By using deliberative democratic theory, this article views that the usage of bot accounts could prevent the objective achievement of democracy based on the 1945 Constitution. The authors recommend the regulation of bot accounts through the revision of Law Number 11 of 2008 concerning Electronic Information and Transactions with bringing up various notable arguments regarding the law implementation.